Cyano group modulated porous carbon nitride assisted by silver nanowire for boosting photoreduction of aqueous Cr(VI). Issue 4 (August 2021) - Wei, Wei; Zhang, Qian; Li, Zeyang; Guo, Zhipeng; Guo, Wei; Wang, Ting; Wei, Ang
Abstract: Rapid recombination of photogenerated electron-hole pairs and low utilization of visible light are still restricting the photoreduction efficiency of aqueous Cr(VI) of graphitic carbon nitride. In this work, cyano group (-C≡N) modulated porous carbon nitride assisted by silver nanowire was successfully constructed. Caused by the intense electron acceptors of -C≡N, the co-existence of both n-type and p-type semiconductor characteristics was exhibited in -C≡N modulated porous carbon nitride. The built-in electric field derived from the -C≡N modulated p-n homojunction was suitable to promote separation of electron-hole pairs and retain photogenerated charges with stronger redox capability. In addition, the assisted silver nanowire further enhanced the visible light harvesting derived from the surface plasmon resonance effect of silver nanowire. As expected, the distinctive design could synergize p-n homojunction and plasmonic metal/semiconductor, which was beneficial to strengthen photocatalytic reduction of aqueous Cr(VI) under visible light. The photocatalyst with the unique structure displayed an enhanced photocatalytic reduction efficiency of aqueous Cr(VI) under visible light in comparison with the pristine graphitic carbon nitride. After 2.5 h visible light irradiation, the aqueous Cr(VI) was almost removed. The visible light photocatalytic reaction rate constant of Cr(VI) over Ag-CN/KOH-2 is about 13.8 times than bulk g-C3 N4 . Graphical Abstract: ga1 Highlights: Cyano group modulated porous carbon nitride assisted by silver nanowire was successfully constructed. The p-type semiconductor characteristic in carbon nitride was derived from the introduced -C≡N. The p-n homojunction was available for separating photogenerated electron-hole pairs. The SPR of the assisted silver nanowire further enhanced the visible-light harvesting. The constructed photocatalyst boosted the photoreduction efficiency of Cr(VI) compared to pristine carbon nitride.